FUNCTION OF CODE SWITCHING USED IN TEACHER’S TALK OF SMA EL-SHADAI MAGELANG IN THE SCHOOL YEAR OF 2017/2018 - Rivan Indra Praditya (Faculty of Education and Teachers Training, 2019)
English is a foreign language in Indonesia. Many people in Indonesia have started to learn it. Due to that, code-switching phenomenon can occur among Indonesians when people learn it. The phenomenon also occurred in the SMA EL-SHADAI Magelang, where the teacher used code-switching to teach English. The teacher did it since the English language was still the foreign language for all primary students there.There were two research questions to be answered. They were 1) what are the function of code switching that are used by the teacher? and 2) what is the dominant function of code switching that are used by the teacher?The researcher used a qualitative method. It was a discourse analysis since it is a study on the language use and sentence. To answer both questions, the data were gathered by observing the teacher when the teacher taught some classes. The teacher was chosen purposely. The data were gathered by observing the teacher. The data identified based on Mattson and Burenhult (1999) theory.